2015
DOI: 10.1002/jaal.425
|View full text |Cite
|
Sign up to set email alerts
|

Writing From Behind the Fence

Abstract: Graphic novels are an increasingly popular format that educators can use as a tool to teach reading and writing skills across the K–12 curriculum. This article describes a project in which incarcerated youths collaborated with a graphic illustrator to create a graphic novel about teens dealing with issues related to HIV/AIDS. The graphic novel is currently being used as an HIV/AIDS education and prevention tool for teens. The article examines the impact that creating a graphic novel had on the literacy lives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…As she had hoped, multimodal storytelling resulted in revision, but it occurred more organically than she ever expected, and it required her to learn new composition strategies alongside her students. Lynn's experience reflects the findings of Owens (2013), Rowsell and Kendrick (2013), and others that multimodal texts can powerfully engage adolescent students, particularly those whose voices have been marginalized (Gavigan & Albright, 2015;Kim, 2016;Park, 2016), but that composing with new media may present additional barriers to access (Rowsell et al, 2017).…”
Section: Engagement Anxiety and Empathymentioning
confidence: 55%
See 1 more Smart Citation
“…As she had hoped, multimodal storytelling resulted in revision, but it occurred more organically than she ever expected, and it required her to learn new composition strategies alongside her students. Lynn's experience reflects the findings of Owens (2013), Rowsell and Kendrick (2013), and others that multimodal texts can powerfully engage adolescent students, particularly those whose voices have been marginalized (Gavigan & Albright, 2015;Kim, 2016;Park, 2016), but that composing with new media may present additional barriers to access (Rowsell et al, 2017).…”
Section: Engagement Anxiety and Empathymentioning
confidence: 55%
“…Emily and Anne advocate for the use of graphic novels, young adult literature, and digital texts such as podcasts in their courses and PD partnerships. Considerable research over the past decade has indicated that reading and writing nontraditional texts such as these have value for engaging adolescent readers (Chisholm, Shelton, & Sheffield, 2017;Owens, 2013;Rowsell & Kendrick, 2013;Smythe & Neufeld, 2010;Vasudevan, Schultz, & Bateman, 2010) and representing FEATURE ARTICLE often marginalized identities (Gavigan & Albright, 2015;Kim, 2016;Park, 2016). Although many teachers and scholars are clearly enthusiastic about embracing multimodal literacies (Hansen, 2012;Rice, 2012;Sewell & Denton, 2011) and developing instructional models for reading and writing multimodal text (Costello, 2012;Meyer & Jiménez, 2017), the case for these texts may not be as settled as this research suggests.…”
mentioning
confidence: 99%
“…For example, involve students in summarizing some paragraphs from their social studies or science textbooks for a specific audience. After summarization, engage students in adding a persuasive/argumentative writing piece to explain the importance of the information presented and engage students in writing their own graphic books (printed or multimodal texts), an approach we have not explored, but based on student enthusiasm for graphic novels, this approach could potentially contribute to motivation in literacy (e.g., Gavigan & Albright, 2015).…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Visual resources have been used to promote health, MHL and wellness for refugee young people: graphic novels (similar to comic books), DVDs, posters and mobile phone apps. Multimedia and arts-based activities also offer refugee youth opportunities to work with and learn from other refugees and with host country youth (Schwarz and Crenshaw, 2011;Ferrari et al, 2015;Gavigan and Albright, 2015). Canadian research indicates that refugee youth are 'likely to take advantage of such opportunities if they were offered' (Edge et al, 2014).…”
Section: Resources To Support Refugee Youth Mhlmentioning
confidence: 99%